Os anos iniciais e o ensino de ciências: dificuldades do trabalho docente em tempos de pandemia - Baccin, Bruna Ambros (2022)
The Early Years of elementary school are the stage responsible for learning the first letters, reading and writing. At this stage, the teaching of science can enable the knowledge of basic concepts of natural sciences, awakening in the student the interest, curiosity and sense of investigation, which will contribute to the intellectual development of the individual. However, teachers face difficulties in their practice due to the numerous issues that permeate their pedagogical work. Thus, the objective of this study was to analyze the difficulties faced by teachers of the Early Years in their practice, before and during the COVID-19 pandemic that caused remote teaching. The proposal was developed in the municipal network of Jaguari, RS, where sixteen teachers participated in the first stage of the study and twenty-one in the second stage. The methodology is characterized as qualitative, of the case study type, in which the research stages are structured based on the five stages of the Arc of Maguerez. Therefore, in the "Observation of reality", a study was carried out in the official documents, interviews, and application of an online questionnaire. In the "Key points", the topics that were deepened in the theorization were established, being: Teacher education; Early years; Initial and continuing education; Science teaching; Difficulties in practice; and, Pandemic. In the "Theorization" a deepening of the points listed in the previous step was carried out. The first one identified the difficulties faced by teachers of the Early Years in their teaching practice, and the results infer that the difficulties are related to the interest and learning of the students, social problems, and the absence of the family at school. Manuscript two investigated the difficulties faced in teaching practice during remote teaching, and the results revealed that the difficulties were lack of teacher and student interaction, lack of internet access, failure to deliver activities, lack of knowledge of digital technologies, and difficulty preparing classes for the remote teaching model. Finally, the "Application to Reality" was the moment to reflect on the results found. It is inferred that the difficulties faced daily by teachers are inherent to their practice, when, because they are immersed in a context of issues that overwhelm them, they do not relate the difficulties faced with their training, nor are able to reflect on their practice. It was also identified that, in the Early Years, teachers have a 'shadowed knowledge' in relation to the teaching of Sciences, due to the prioritization of other areas of knowledge, such as Portuguese and Mathematics, present in the large-scale evaluations, because of daily, social and family issues, and the difficulties of their own practice. Among the results, it is pointed out that the accomplishment of formative processes, aiming at the reflection on the teaching, can sensitize teachers to develop a contextualized science teaching, close to the students' reality.